Organizational Secrecy and the FBI's COINTELPRO–Black Nationalist Hate Groups Program, 1967-1971. (November 2015) - Hoerl, Kristen; Ortiz, Erin
In this article, we explain how secrecy influenced the communication and decision-making processes within COINTELPRO-Black Nationalist Hate Groups, the FBI's covert program to disrupt left-leaning Black political organizations between 1967 and 1971. Memos exchanged between the FBI Director and field offices reveal how the organization strategized to conceal its identity as the source of anonymous communication. The Bureau developed explicit techniques for managing the content of their messages, the materials used to construct print messages, and the distribution of those messages. The Bureau's techniques suggest that organizational secrecy involves a high degree of coordination between members, but it may also endanger the organization's longevity and the public welfare.